Complexation of hydroxytyrosol and 3, 4-dihydroxyphenylglycol with pectin and their potential use for colon targeting. (1st May 2017) - Bermúdez-Oria, Alejandra; Rodríguez-Gutiérrez, Guillermo; Rubio-Senent, Fátima; Lama-Muñoz, Antonio; Fernández-Bolaños, Juan
Highlights: Pectin-based formulations entrap water soluble olive phenolic compounds, HT & DHPG. In vitro release of HT and DHPG from beads in simulated gastric fluid was studied. Olive oil-entrapped Ca pectin-alginate beads is a good system for colon targeting. An important amount of HT and DHPG were immobilized by interaction with pectin. The existence of this HT-pectin complex was confirmed by MALDI TOF–TOF analysis. Abstract: Hydroxytyrosol (HT) and 3, 4-dihydroxyphenylglycol (DHPG) are two phenolic antioxidants naturally found in olive fruit with anti-inflammatory properties. This study explored the interaction of pectin with HT and DHPG via their encapsulation into pectinate beads. Purification by size exclusion chromatography, changes in the fluorescence spectrum of the HT and pectin, and MALDI TOF–TOF analysis suggested the existence of the phenol-pectin complexes. The entrapment efficiency, swelling properties, and in vitro release of HT and DHPG of the beads were studied. The results show that the beads can entrap the water soluble compounds HT and DHPG in sufficient amounts to reach the colon. The beads consisted of an important amount of pectin-bound HT or DHPG after two hours at gastric pH. This study highlights the potential use of HT-and DHPG-loaded pectinate gel beads for the colon-targeted delivery of these bioactive compounds to help prevent or relieve chronic inflammatory bowel disease.